2019
DOI: 10.1080/19768354.2019.1583126
|View full text |Cite
|
Sign up to set email alerts
|

VNN3 is a potential novel biomarker for predicting prognosis in clear cell renal cell carcinoma

Abstract: Although pathological observations provide approximate prognoses, it is difficult to achieve prognosis in patients with existing prognostic factors. Therefore, it is very important to find appropriate biomarkers to achieve accurate cancer prognosis. Renal cell carcinoma (RCC) has several subtypes, the discrimination of which is crucial for proper treatment. Here, we present a novel biomarker, VNN3, which is used to prognose clear cell renal cell carcinoma (ccRCC), the most common and aggressive subtype of kidn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Enriched genes such as HGF (hepatocyte growth factor) [Purcell et al 2011], ABCB11 [Vilarinho et al 2014] and TLR4 [Hsiao et al 2015] were linked with advancement of hepatoblastoma. Enriched genes such as VNN3 [Ha et al 2019], HPGD (15-hydroxyprostaglandin dehydrogenase) [He et al 2016], VNN2 [Chen et al 2018], VNN1 [Zhang et al 2017], GPD1 [Zhou et al 2017], CFH (complement factor H) [Campa et al 2015], SERPINA3 [Cao et al 2018], AFM (afamin) [Shen et al 2016], HPR (haptoglobin-related protein) [Epelbaum et al 1998], C4BPA [Sogawa et al 2016], CYP4Z1 [Zheng et al 2019], SRD5A1 [Sinreih et al 2015] and STEAP4 [Xue et al 2017] were linked with progression of various cancer types, but these genes may be involved in development of hepatoblastoma. Low expression of enriched genes such as ETFDH (electron transfer flavoprotein dehydrogenase) [Wu et al 2019], GNMT (glycine N-methyltransferase) [Chen et al 1998], DCN (decorin) [Ju et al 2015], ITIH4 [Li et al 2018], GHR (growth hormone receptor) [Qi et al 2016], LYVE1 [Kitagawa et al 2013] and HP (haptoglobin) [Mondal et al 2016] were identified with development of hepatocellular carcinoma, but decrease expression of these genes may be associated with development of hepatoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Enriched genes such as HGF (hepatocyte growth factor) [Purcell et al 2011], ABCB11 [Vilarinho et al 2014] and TLR4 [Hsiao et al 2015] were linked with advancement of hepatoblastoma. Enriched genes such as VNN3 [Ha et al 2019], HPGD (15-hydroxyprostaglandin dehydrogenase) [He et al 2016], VNN2 [Chen et al 2018], VNN1 [Zhang et al 2017], GPD1 [Zhou et al 2017], CFH (complement factor H) [Campa et al 2015], SERPINA3 [Cao et al 2018], AFM (afamin) [Shen et al 2016], HPR (haptoglobin-related protein) [Epelbaum et al 1998], C4BPA [Sogawa et al 2016], CYP4Z1 [Zheng et al 2019], SRD5A1 [Sinreih et al 2015] and STEAP4 [Xue et al 2017] were linked with progression of various cancer types, but these genes may be involved in development of hepatoblastoma. Low expression of enriched genes such as ETFDH (electron transfer flavoprotein dehydrogenase) [Wu et al 2019], GNMT (glycine N-methyltransferase) [Chen et al 1998], DCN (decorin) [Ju et al 2015], ITIH4 [Li et al 2018], GHR (growth hormone receptor) [Qi et al 2016], LYVE1 [Kitagawa et al 2013] and HP (haptoglobin) [Mondal et al 2016] were identified with development of hepatocellular carcinoma, but decrease expression of these genes may be associated with development of hepatoblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…With the advanced development of high‐throughput sequencing in recent years, numerous studies have screened numerous useful biomarkers for predicting prognosis or therapeutic targets, including methylation markers, signaling pathway alterations, as well as mutation drivers. However, genome‐wide screening of lncRNAs based on large samples from muticenters were less reported, especially in kidney malignancies . ccRCC is the most common pathologic subtypes of kidney cancer associated with high morbidity and mortality, possessing an aggressive and metastasis traits due to various molecular and cellular heterogeneity .…”
Section: Discussionmentioning
confidence: 99%
“…However, genome-wide screening of lncRNAs based on large samples from muticenters were less reported, especially in kidney malignancies. [14][15][16] ccRCC is the most common pathologic subtypes of kidney cancer associated with high morbidity…”
Section: Discussionmentioning
confidence: 99%
“…Microglia cells are also possibly involved in such interactions with T. gondii via this type of signaling. VNN3, also called vascular non-inflammatory molecule 3, is reportedly a potential prognostic biomarker for clear cell renal cell carcinoma [70], but no relationship with T. gondii infection has been reported thus far. Interestingly, Ppfibp2, another top-ranking gene, currently has an unknown function and unknown relationship with T. gondii infection.…”
Section: Discussionmentioning
confidence: 99%